Body condition, live weight and success in agonistic encounters in mixed parity groups of sows during gestation. (2nd July 2018) - Norring, M.; Valros, A.; Bergman, P.; Marchant-Forde, J. N.; Heinonen, M.
Abstract : Group housing of gestating sows benefits their welfare by allowing them freedom of movement and the opportunity for social interaction. However, social life could also bring disadvantages for individuals who receive direct aggression or are displaced from the feeder. The aim of this study was to investigate associations between social behaviour, body condition and live weight. Gestating sows ( n =298) were investigated on a commercial farm. Sows were housed in mixed parity groups where two single space, ad libitum trough feeders served 12 animals. Sows were weighed, body condition scored and had their back fat layer measured at mixing, 4 weeks after insemination and again before farrowing. Social status was estimated based on the numbers of won and lost agonistic interactions at mixing and at the end of gestation. In addition, tear staining was scored before the farrowing and reproductive performance data were collected. With the aid of video recordings, 100 to 150 interactions per group were observed. Winning percentage at mixing and at the end of gestation were associated ( P <0.05) and appeared relatively stable within individuals. Tear staining scores and litter sizes were not associated with winning percentage at the end of gestation. However, live weight, relative weight, body condition and back fat thickness were associated with winning percentage ( P <0.05), giving heavier animals an advantage. Low winning percentage related to lower live weight gain, probably due to poorer success in competition for feed. Live weight within a mixed parity group could be used as a proxy measure for social status. Sows with low body condition score and submissive sows might need special attention with regard to group dynamics and housing to alleviate the effects of competition in group housing.